2003
DOI: 10.1023/a:1024292831762
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The psychostimulant caffeine promotes behavioral effects such as hyperlocomotion, anxiety, and disruption of sleep by blockade of adenosine receptors. The availability of extracellular adenosine depends on its release by transporters or by the extracellular ATP catabolism performed by the ecto-nucleotidase pathway. This study verified the effect of caffeine on NTPDase 1 (ATP diphosphohydrolase) and 5'-nucleotidase of synaptosomes from hippocampus and striatum of rats. Caffeine and theophylline tested in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…It is possible that caffeine leads to Rad51 eviction by stimulating Rad51 to hydrolyze ATP, analogous to results in other systems ( 70 , 71 ). We therefore used a rad51 Δ strain complemented by a centromere-containing plasmid with rad51-K191R expressed from its endogenous promoter to test for the involvement of ATP hydrolysis in dissociation of Rad51 filaments (Supplementary Figure S2A and B).…”
Section: Resultssupporting
confidence: 57%
“…It is possible that caffeine leads to Rad51 eviction by stimulating Rad51 to hydrolyze ATP, analogous to results in other systems ( 70 , 71 ). We therefore used a rad51 Δ strain complemented by a centromere-containing plasmid with rad51-K191R expressed from its endogenous promoter to test for the involvement of ATP hydrolysis in dissociation of Rad51 filaments (Supplementary Figure S2A and B).…”
Section: Resultssupporting
confidence: 57%
“…A preliminary dose analysis indicated that higher concentrations of caffeine were not well tolerated. Bottles were changed every 2-3 days as described previously (Boeck et al, 2009; da Silva et al, 2003). …”
Section: Methodsmentioning
confidence: 99%